At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Certainly! Let's write the given product [tex]\( 12 \cos (8q) \sin (7q) \)[/tex] as a sum using trigonometric identities. We will use the product-to-sum formulas, specifically, the identity:
[tex]\[ \sin(A)\cos(B) = \frac{1}{2}[\sin(A+B) + \sin(A-B)] \][/tex]
Here, [tex]\( A = 7q \)[/tex] and [tex]\( B = 8q \)[/tex]. Therefore:
[tex]\[ \cos(8q) \sin(7q) = \frac{1}{2}[\sin(7q + 8q) + \sin(7q - 8q)] = \frac{1}{2}[\sin(15q) + \sin(-q)] \][/tex]
Since [tex]\( \sin(-x) = -\sin(x) \)[/tex], we can rewrite [tex]\( \sin(-q) \)[/tex]:
[tex]\[ \sin(-q) = -\sin(q) \][/tex]
Now, substituting this back into our formula, we get:
[tex]\[ \cos(8q) \sin(7q) = \frac{1}{2}[\sin(15q) - \sin(q)] \][/tex]
We need to multiply this expression by 12 to get the original expression:
[tex]\[ 12 \cos(8q) \sin(7q) = 12 \cdot \frac{1}{2}[\sin(15q) - \sin(q)] \][/tex]
[tex]\[ = 6[\sin(15q) - \sin(q)] \][/tex]
[tex]\[ = 6\sin(15q) - 6\sin(q) \][/tex]
Thus, the expression [tex]\( 12 \cos(8q) \sin(7q) \)[/tex] written as a sum is:
[tex]\[ 12 \cos(8q) \sin(7q) = 6\sin(15q) - 6\sin(q) \][/tex]
This is your final answer.
[tex]\[ \sin(A)\cos(B) = \frac{1}{2}[\sin(A+B) + \sin(A-B)] \][/tex]
Here, [tex]\( A = 7q \)[/tex] and [tex]\( B = 8q \)[/tex]. Therefore:
[tex]\[ \cos(8q) \sin(7q) = \frac{1}{2}[\sin(7q + 8q) + \sin(7q - 8q)] = \frac{1}{2}[\sin(15q) + \sin(-q)] \][/tex]
Since [tex]\( \sin(-x) = -\sin(x) \)[/tex], we can rewrite [tex]\( \sin(-q) \)[/tex]:
[tex]\[ \sin(-q) = -\sin(q) \][/tex]
Now, substituting this back into our formula, we get:
[tex]\[ \cos(8q) \sin(7q) = \frac{1}{2}[\sin(15q) - \sin(q)] \][/tex]
We need to multiply this expression by 12 to get the original expression:
[tex]\[ 12 \cos(8q) \sin(7q) = 12 \cdot \frac{1}{2}[\sin(15q) - \sin(q)] \][/tex]
[tex]\[ = 6[\sin(15q) - \sin(q)] \][/tex]
[tex]\[ = 6\sin(15q) - 6\sin(q) \][/tex]
Thus, the expression [tex]\( 12 \cos(8q) \sin(7q) \)[/tex] written as a sum is:
[tex]\[ 12 \cos(8q) \sin(7q) = 6\sin(15q) - 6\sin(q) \][/tex]
This is your final answer.
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.